Integrating Fire Prevention Strategies with Industrial Hygiene to Improve Workplace Safety in the textile industry PT. Panca Bintang Tunggal - Utomo, Bekti; Sumardiyono; Widjanarti, Maria Paskanita; Nisa, Farhana Syahrotun; Ismayenti, Lusi; Rinawati, Seviana; Atmojo, Tutug Bolet; Rha, Warda Yussy; Gustav, Jordan Syah (Yayasan Ilomata, 2025)
In addressing workplace safety within PT. Panca Bintang Tunggal, a qualitative approach was employed to explore the integration of fire prevention strategies with industrial hygiene. This research distinguishes itself from existing literature by focusing specifically on the integration of fire prevention strategies with industrial hygiene practices tailored for PT. Panca Bintang Tunggal. Previous studies often address these areas in isolation, neglecting the synergistic benefits of their integration. Data was collected through semi-structured interviews with 50 participants, including safety officers, production managers, and frontline workers. This diverse participant pool ensures a comprehensive perspective on safety practices and fire hazards prevalent in the workplace. The data analysis involved thematic coding, where responses were categorised into key themes such as risk perception, existing safety measures, and the effectiveness of current fire prevention strategies. Thematic analysis is particularly valuable in qualitative research as it helps in identifying patterns and insights that quantitative methods may overlook. The findings indicate a pressing need for integrated training programs that encompass both fire prevention and industrial hygiene practices. For example, implementing regular fire drills alongside hygiene training can reinforce the importance of safety protocols, fostering a culture of safety within the organisation. As noted by the National Fire Protection Association, organisations with comprehensive training programmes significantly reduce the incidence of workplace fires.